Small and medium enterprises survival during the global crises: a systematic review of theoretical perspectives of building resilience in the time of crisis - Saadan Mohamed Senin; Noor Hasni Juhdi; Ahmad Raflis Che Omar; Noor Azuan Hashim (Cogent Business & Management, 2024)
Given that small and medium-sized enterprises (SMEs) are the backbone of the economy, SME survival and resilience are vital during financial, health, or social crises, such as war or political upheaval. The current study conducted a systematic literature analysis from theoretical perspectives supporting SME survival during a crisis. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) systematic review was performed, including literature from SCOPUS, Web of Science (WoS) and Google Scholar. Out of the 40 reviewed papers, the top five most commonly used theories to ensure SME resilience and survival were resource-based views, competitive advantage, leadership, entrepreneurial and innovation theories. The first paper in the review was from 2003 with research spanning up to 2022. The literature also employed quantitative, qualitative and mixed methodologies where most approaches were quantitative. Tangible and intangible resources, effective leadership, competitive advantage, entrepreneurial innovativeness and a combination of these resources could confirm long-term survival among SMEs during crises. Organisational survival in times of crisis is important and strategies must be examined for preparation in the future. Despite its importance, few studies have considered this domain. Therefore, this study is a significant contribution to the literature because it is one of few attempts that highlights the SMEs vulnerability during survival.
Keywords: 650; Global crises; health crisis; terrorism; war; financial crisis; SMEs; SMEs survival; post Covid-19; entrepreneurial innovativeness; SMEs resilience